Comparison of Enzyme-Linked Immunosorbent Assay and Chemiluminescence Immunoassay for Thyroid Stimulating Hormone Analysis in Tertiary Care Hospital Lahore - Dr.Nusrat Alavi; Dr Aneela Khawaja; Dr. Maliha Asif; Dr Asma Ejaz; Dr Abeer; Faiqa Arshad (Aziz Fatimah Medical and Dental College, 2021)
Objective: To compare enzyme-linked immunosorbent assay and Chemiluminescence immunoassay for thyroid stimulating hormone analysis in human serum.   Methodology: This cross-sectional study conducted from 17th March till 13th June. In Punjab Rangers Teaching Hospital, Lahore after approval from Institutional Review Board.  Random samples from both genders, between 18-70 years of age were included. Haemolysed, lipemic or icteric specimens were excluded. The sera were assayed for thyroid stimulating hormone (TSH) by enzyme-linked immunosorbent assay (ELISA) and Chemiluminescence immunoassay (CLIA). Data was analyzed by SPSS 24. Results: A total of one hundred and ninety-eight serum samples were processed by ELISA and CLIA in all the samples, with more females as compared to males (1:1.3). ELISA technique identified 134 subjects as Euthyroid, 40 Hypothyroid and 24 Hyperthyroid, while 122 Euthyroid, 48 hypothyroid and 28 hyperthyroid subjects by CLIA. Thyroid stimulating hormone (TSH) levels reference range was taken 0.4-4.5mU/L according to American Thyroid Association. Mean ± SD of TSH was 1.45 ± 0.79; 12.27 ± 11.03 and 0.23 ± 0.17 mU/L respectively by ELISA whereas CLIA indicated Mean ± SD to be 1.93 ± 0.936, 16.04 ± 14.68 and 0.393 ± 0.375 mU/L respectively for Euthyroid, hypothyroid and hyperthyroid. Correlation of coefficient (R2 =0.89) was found significantly positive between both methods. There was a significant difference in hypothyroid and Euthyroid groups. Conclusion: TSH assay by CLIA has shown a wider range of functionality, throughout and borderline cases were identified better as compared to ELISA. Turn-around-time (TAT) decreased, physician satisfaction increased and indirectly benefitting patient treatment and prognosis.